Marginal Identity Representation of Minority Language Groups in Fiction at Wattpad Indonesia - Syukrina Rahmawati (Angstrom Centre of Education, 2025)
This research examines the representation of marginalized identities of language minority groups in digital fiction on Wattpad Indonesia. The problem discussed in this research is how these identities are represented and fought for in a broader social and cultural context. The material objects of the research are two works of fiction on the Wattpad Indonesia platform entitled Dihantui Mas Mantan and Bandung: Kisahku Dengan anak ITB. Both combine two languages, namely Indonesian and local languages, in the story's elements. This research identifies representation strategies that connect language, identity, and social context. The research approach used is descriptive qualitative approach. The results show that the Wattpad Indonesia platform allows writers to express their existence, although it is often marginalized in public discourse. Three social environmental factors also influence this, namely social stigma, language policy, and mainstream representation. In addition, this research highlights the positive and negative impacts of digital interaction and how digital fiction can be a tool to fight for the recognition and visibility of minority language groups.